Biomass thermochemical conversion in small scale facilities - Heredia Salgado, Mario Alejandro (2020)
The energetic conversion of the residual biomass generated in the Ecuadorian agro-industrial sector is an alternative to reduce the consumption of fossil fuels in thermal appliances, mitigate the environmental impacts associated with improper residues disposition and to reduce the agroindustry dependency on subsidies to fossil fuels. In general, most of the residual biomass generated in the agro-industrial sector would have at least one of these characteristics: high ash content and low bulk density. Combustion of low bulk density biomass in the horizontal burner prototype (HBP) developed in this study show to be problematic. Conveying issues (e.g. stagnation and dome formation) and fuel dragging by the combustion air stream produced instabilities in the flame front and prevented a steady combustion process. From the agro-residues analyzed in this study, only palm oil kernel shells (KS) can be converted into thermal energy observing the European eco-design standards, that is, the CO concentration in the flue gas was below 250 mg/Nm3 (values corrected to 11% vol. O2, dry gas). Nonetheless, the ash management within the combustion process must be improved. It was observed that a pyrolysis process, that is, the pyrolysis small and modular auger reactor developed in this thesis can make effective use of most of the low density and high ash content agro-residues considered in this study. Auto-thermal operating conditions were observed when the feedstock of the pyrolysis process was KS. In these conditions, the CO concentration in the flue gas (197 mg/Nm3 at 11% vol. O2, dry gas) was lower than the limit established by the European eco-design standards. For the rest of the agro-residues considered in this study (coffee husks, quinoa stems, and quinoa husks) the pyrolysis gas combustion process took place under cocombustion conditions, that is, a constant thermal energy input is required to keep steady temperatures in the combustion and pyrolysis processes. It is observed that the physicochemical properties of the produced biochar changes according to the feedstock and reactor operating conditions. However, in all the cases the molar H/Corg and O/Corg ratios agree with the guidelines for the sustainable production of biochar. It is further observed that the exergy efficiency of charcoal production is around 65.5%. This estimation considers a fully integrated system was the excess thermal energy generated during carbonization is used to produce work (e.g. drying). The reference payback period associated with a pyrolysis facility in Ecuador assuming a biochar price between 3.5 to 5.3 USD/t would range between 3 to 5 years. However, a high uncertainty concerning the biochar market price is recognized. In general, fossil fuel subsidies hinder the transition towards the use of residual biomass as an energy source. Regardless of changes in the subsidies policy, the increase of the exergy efficiency and the optimization of the capital and operation costs associated with the biomass valorization infrastructures are alternatives to promote the sustainable utilization of the residual biomass generated in the studied agro-industrial sectors.